The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1090/s0002-9939-1992-1079889-7
|View full text |Cite
|
Sign up to set email alerts
|

Generic spectral properties of measure-preserving maps and applications

Abstract: Abstract.Let 3? denote the group of all automorphisms of a finite Lebesgue space equipped with the weak topology. For T e S£ , let 177-denote its maximal spectral type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 12 publications
(1 reference statement)
1
16
0
Order By: Relevance
“…Similar problems to what we consider here were taken up in [5]. It was shown that for a typical automorphism and any k 1 , .…”
Section: Corollary 1 the Answer For (3) Is Positive Whenever (4) Holsupporting
confidence: 53%
See 1 more Smart Citation
“…Similar problems to what we consider here were taken up in [5]. It was shown that for a typical automorphism and any k 1 , .…”
Section: Corollary 1 the Answer For (3) Is Positive Whenever (4) Holsupporting
confidence: 53%
“…(ii) If α + β > 1, then T ⊥ S. 5 Let α ∈ (0, 1) and let S 1 , S 2 be ergodic flows on (Y 1 , C 1 , ν 1 ) and (Y 2 , C 2 , ν 2 ), respectively.…”
Section: Jp Property As a Weaker Version Of Disjointnessmentioning
confidence: 99%
“…The disjointness of the convolution powers follows from α-weakly mixing property when 0 < α < 1 (see [6] and [7]). This property is widely used in ergodic theory to build counterexamples ( [8]). The question of α-weak mixing for Chacon's automorphism can be considered as a special case of the general problem of description of the weak limits of powers ofT .…”
Section: Introductionmentioning
confidence: 99%
“…The main spectral property of a generic T ∈ Aut(X, µ) is given by Del Junco-Lemańczyk [3] where Aut(X, µ) is the set of all measure preserving transformations on a Borel measure space (X, µ). They proved that for a generic T ∈ Aut(X, µ), for every k(1), k(2), .…”
Section: Introductionmentioning
confidence: 99%
“…
Del Junco-Lemańczyk [3] showed that a generic measure preserving transformation satisfies a certain orthogonality conditions. More precisely,
…”
mentioning
confidence: 99%